2020
DOI: 10.1001/jamapsychiatry.2019.3523
|View full text |Cite
|
Sign up to set email alerts
|

Incidence Rates and Cumulative Incidences of the Full Spectrum of Diagnosed Mental Disorders in Childhood and Adolescence

Abstract: IMPORTANCE Knowledge about the epidemiology of mental disorders in children and adolescents is essential for research and planning of health services. Surveys can provide prevalence rates, whereas population-based registers are instrumental to obtain precise estimates of incidence rates and risks.OBJECTIVE To estimate age-and sex-specific incidence rates and risks of being diagnosed with any mental disorder during childhood and adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
263
4
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 321 publications
(303 citation statements)
references
References 70 publications
31
263
4
5
Order By: Relevance
“…The SNP-based h 2 results for ADHD and ASD were similar albeit somewhat higher for both LDSC and LDAK when using estimates based on a Danish child-specific study [19], compared to using prevalence estimates from the whole Danish population [18]; see Tables S4 and S5.…”
Section: Sex-stratified Snp-based H 2 Estimates and Assessment Of Sexmentioning
confidence: 87%
See 1 more Smart Citation
“…The SNP-based h 2 results for ADHD and ASD were similar albeit somewhat higher for both LDSC and LDAK when using estimates based on a Danish child-specific study [19], compared to using prevalence estimates from the whole Danish population [18]; see Tables S4 and S5.…”
Section: Sex-stratified Snp-based H 2 Estimates and Assessment Of Sexmentioning
confidence: 87%
“…Additionally, these prevalence estimates may not generalize to populations outside of the USA. Therefore, we also used sex-specific cumulative incidence rates at age 50 years, based on individuals identified through inpatient and outpatient care in Denmark [18], as well as childhood-specific (age <18 years) estimates for the 2 neurodevelopmental disorders in our analyses (ADHD & ASD), based on a more recent Danish study, as the discovery GWAS for these traits were based on samples of mostly children [19]; see Table S2.…”
Section: Sex-specific Trait Prevalencementioning
confidence: 99%
“…In addition, children with ADHD are at increased risk of a range of adverse outcomes , including the development of substance use disorders (SUD) . In general, the risk of SUD increases through adolescence, to reach its maximum during early adulthood , with a faster progression rate in ADHD than in the general population . In individuals with ADHD, known predictors of SUD include persistent ADHD , being diagnosed with ADHD in later adolescence or adulthood , and co‐occurrence of oppositional defiant disorder and conduct disorder (ODD/CD) .…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is a critical developmental stage for the onset of psychological difficulties and mental health problems, ranging from transient mild symptoms to full-blown anxiety disorders [2]. The core challenge in this age span is the derivation of developmentally more sensitive assessment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescence is considered a crucial developmental stage with different transformations that impact physical, psychological and sociological levels [1]. Related to these changes, different authors have revealed that there is an increase in psychological difficulties ranging from transient mild symptoms to full-blown anxiety disorders [2]. For instance, prevalence rates of depression and anxiety increase at this time [3,4], and it has also been documented that adolescents are at a higher risk of emotional and behavioral difficulties [5].…”
Section: Introductionmentioning
confidence: 99%